Smart Structures and Materials 2004: Smart Structures and Integrated Systems 2004
DOI: 10.1117/12.540013
|View full text |Cite
|
Sign up to set email alerts
|

Design, fabrication, and testing of SMA-enabled adaptive chevrons for jet noise reduction

Abstract: This study presents the status and results from an effort to design, fabricate, and test an adaptive jet engine chevron concept based upon embedding shape memory alloy (SMA) actuators in a composite laminate, termed a SMA hybrid composite (SMAHC). The approach for fabricating the adaptive SMAHC chevrons involves embedding prestrained Nitinol actuators on one side of the mid-plane of the composite laminate such that thermal excitation generates a thermal moment and deflects the structure. A glass-epoxy pre-preg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
4
1

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 10 publications
0
21
0
Order By: Relevance
“…Previous work by the present authors demonstrated the feasibility of the active SMAHC chevron concept [23][24][25] . That work also provided the first shape control experimental validation for a recently commercialized (MSC.Nastran and ABAQUS) constitutive model for SMAHC materials and structures [25][26][27][28] .…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Previous work by the present authors demonstrated the feasibility of the active SMAHC chevron concept [23][24][25] . That work also provided the first shape control experimental validation for a recently commercialized (MSC.Nastran and ABAQUS) constitutive model for SMAHC materials and structures [25][26][27][28] .…”
Section: Introductionmentioning
confidence: 95%
“…Previous work at NASA LaRC presented a fabrication approach, test results, and validation of a numerical model for a SMAHC chevron concept with a single embedded actuator assembly 23,25 . It was found that the single actuator assembly provided insufficient actuation authority and limitations of the fabrication approach dictated development of a new procedure for embedding multiple actuators.…”
Section: Smahc Chevron Fabricationmentioning
confidence: 99%
“…Previous work by the present authors demonstrated the feasibility of the active SMAHC chevron concept using a flat prototype, i.e., without the cylindrical radius of curvature [20][21][22][23] . That work also provided the first shape control experimental validation for a recently commercialized (MSC.Nastran and ABAQUS) constitutive model for SMAHC materials and structures [24][25][26][27] .…”
Section: Introductionmentioning
confidence: 96%
“…This topic is currently of significant interest for a variety of advanced aerospace vehicle applications, e.g., see a related publication 15 . Note that use of the ECTE model for shape control applications should be limited to cases in which the recovered strain of the SMA actuators is small relative to the prestrain, unless accommodations are made to schedule diminishment of actuation authority.…”
Section: Cantilevered Smahc Beammentioning
confidence: 99%